An Inquiry into the Managerial Competencies of Islamic Senior High School of Nurul Islam Principal at Mataram, West Nusa Tenggara - Zobi Mazhabi; Muhammad Yunus; Abdul Hamid Aly; Yoyok Amirudin (IJELR: International Journal of Education, Language, and Religion, 2021)
This study aimed at investigating the key management competencies of Islamic Senior High School Nurul Islam West Nusa Tenggara, how the managerial competence of Nurul Islam principal in term of planning, organizing, leading, and controlling also the teacher conception regarding to the issues. In doing so, the study applied qualitative design of case study model. The data gathered through semi-structured interview by involving the principal and one teacher. The zoom meeting platform was utilized to interview the targeted principals. The data were interpreted by applying inductive content analysis technique. Align with the result of data interpretation, having clear and measurable vision and mision, having good teaching and learning program, having criteria for efective learning environtment, involving four frame of leadership style, excuting good administration management process and control are the array of aspects that should be considered by a principle in conducting management in Islamic Senior High School of Nurul Islam.